Augustine's Predestination Doctrine of Hippo: The Legacy of Patristic Theology and Its Implications for Christian Education - Robert Stefanus Hia (International Journal Labs, 2025)
This study discusses the concept of predestination according to Augustine of Hippo and its implications for Christian education. Augustine asserts that humans, because of original sin, are incapable of achieving salvation through their own efforts; only God's sovereign grace is the basis for salvation. His thinking arose from debates with Pelagianism, which emphasized human freedom. Augustine, on the other hand, highlighted the total depravity of humans and their need for God's grace. This doctrine of predestination then affirms the dynamic relationship between God's grace and the limitations of human free will. This study uses a qualitative method with a literature approach. The results of this study show that Christian education is a means of God's grace, whereby God saves, shapes, and restores students to know God. Therefore, Augustine's doctrine of predestination also emphasizes that the goal of Christian education must be oriented towards the transformation of faith, shaping students in obedience and love for God. Thus, Augustine's idea emphasizes that the goal of Christian education is the renewal of life in Christ, not just intellectual achievement.